Liana Diversity In The Northern Region Of Peninsular Malaysia - Johari, Mohamad Syafiq Mohd (2018)
The major aim of this study were to identify and enumerate lianas existence in terms of species, family compositions and their abundance in the four states of the Northern Peninsular Malaysia, namely Perak, Perlis, Penang and Kedah. In Perak, the study was conducted in Belum-Temengor Forest Complex followed by Perlis (Perlis State Park), Penang (Bukit Panchor Forest Reserve) and Kedah (Gunung Jerai). It took one year (October 2015 - October 2016) to investigate, observe and accomplish the sampling for all study sites. Two study cases were deployed to investigate the diversity of lianas following human disturbance occurred towards them and to contemplate the association of lianas with elevation and edaphic factors.